Gen Z Behavioral Intentions to Pay Zakat : The Effect Ease of Digital Payments Zakat Literacy and Religiosity - Indra Kurniawan; Dzikrulloh Dzikrulloh (JOURNAL OF SHARIA ECONOMICS, 2023)
This research aims to examine the influence of ease of digital payments, zakat literacy and religiosity on the behavior intentions of the generation to pay zakat through zakat management organizations. This research uses structural analysis Equation Model-Partial Least Square ( SEM-PLS). The research used a questionnaire data collection technique which was distributed online to Generation Z Muslims , with a total of 199 respondents or samples. The results of this research show that the variables of ease of digital payments and religiosity have a significant effect on generation Z's behavioral intentions to pay zakat through zakat management organizations. Meanwhile, the zakat literacy variable has no effect on generation Z's behavioral intentions to pay zakat through zakat management organizations. Overall, behavior intentions to pay zakat through zakat management organizations is explained by the variables ease of digital payment, zakat literacy, and religiosity at 31.1%, the remaining 68.9% is influenced by other variables outside this research.